2018
DOI: 10.1111/jorc.12257
|View full text |Cite
|
Sign up to set email alerts
|

Nephrology nurses' perceptions of discussing sexual health issues with patients who have end‐stage kidney disease

Abstract: These findings provide an understanding of Thai nurses' perceptions about the challenges in communicating with patients experiencing ESKD regarding sexual health problems and concerns. The findings suggest that sexual health education and training would enhance the confidence of Thai nephrology nurses in initiating sexuality-related discussions with their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 13 publications
2
24
0
Order By: Relevance
“…A total of four studies published between January 2009 and 2020 were included in this scoping review. Two studies used a cross‐sectional design (Green et al, 2012; Van Ek et al, 2018) and two used an interpretive phenomenological design (Hough et al, 2019; Yodchai et al, 2018). The studies were conducted in the United States of America, Netherlands, United Kingdom, and Thailand involving medical and nursing staff.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of four studies published between January 2009 and 2020 were included in this scoping review. Two studies used a cross‐sectional design (Green et al, 2012; Van Ek et al, 2018) and two used an interpretive phenomenological design (Hough et al, 2019; Yodchai et al, 2018). The studies were conducted in the United States of America, Netherlands, United Kingdom, and Thailand involving medical and nursing staff.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 82% of respondents indicated that they had no prior training about sexual dysfunction in kidney failure, and this contributed to them avoiding discussing the topic with patients (Green et al, 2012). Similarly, Yodchai et al (2018) identified that renal nurses reported having a lack of training and knowledge about sexual health, wellbeing, and function and this made them hesitant to discuss sexual health concerns with patients. Specific training and education about sexual health are important in enabling renal nurses to feel confident engaging in discussions with patients about sexual wellbeing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore nurses' experiences of communicating with patients with an indwelling urinary catheter about sexual quality of life. Nurses who discussed SSH with their patients viewed this task as part of their professional responsibility to alleviate patients' and family members' suffering [32]. They tend to use various strategies to approach the subject; for example, they look for appropriate moments, e.g., in a private room [32] and when discussing physical problems or treatment [33][34][35][36].…”
Section: Baker-green (2017) Ukmentioning
confidence: 99%
“…13 Similarly, a minority of nephrology nurses discuss sexual health with their dialysis patients due to barriers of ethnicity, religion, and older age of the patient, 30 as well as inadequate training and lack of suitable time and setting to discuss this sensitive topic. 31 Together, these patterns may translate into difficulties with enrollment of persons with CKD and sexual dysfunctions into research studies. Until the public and those in the scientific and clinical communities accept that these stigmas exist, patient recruitment and prioritization of these studies in CKD research will remain challenging.…”
Section: Barrier 2: Stigma Of Sexual Dysfunctionmentioning
confidence: 99%